The COVID-19 Data Exchange Platform of the German University Medicine - Prokosch, Hans-Ulrich; Bahls, Thomas; Bialke, Martin; Eils, Jürgen; Fegeler, Christian; Gründner, Julian; Haarbrandt, Birger; Hampf, Christopher; Hoffmann, Wolfgang; Hund, Hauke; Kampf, Marvin; Kapsner, Lorenz; et al. (Challenges of Trustable AI and Added-Value on Health, 2022)
COVID-19 has challenged the healthcare systems worldwide. To quickly identify successful diagnostic and therapeutic approaches large data sharing approaches are inevitable. Though organizational clinical data are abundant, many of them are available only in isolated silos and largely inaccessible to external researchers. To overcome and tackle this challenge the university medicine network (comprising all 36 German university hospitals) has been founded in April 2020 to coordinate COVID-19 action plans, diagnostic and therapeutic strategies and collaborative research activities. 13 projects were initiated from which the CODEX project, aiming at the development of a Germany-wide Covid-19 Data Exchange Platform, is presented in this publication. We illustrate the conceptual design, the stepwise development and deployment, first results and the current status.
EVALuna2:507828